MAGNETISM OF THE EARTH'S CRUST UPPER PART: NATURAL AND TECHNOGENIC COMPONENTS - Menshov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The state of the problem of soils magnetic investigations at the present development stage is considered. The examples of polluted soils magnetic studies for solving environmental tasks are given. The Magnetotactic Bacteria role as a non-polluted soil magnetism sources is investigated.